Características clínicas e epidemiológicas dos doadores de sangue infectados pelo SARS-Cov-2 do Hemocentro do Amazonas - Castro, Tiane Sena de (2023)
Covid-19 is an infectious disease caused by the new coronavirus SARS-CoV-2, responsible for causing the biggest pandemic of the century. The disease presents clinical signs of infection at different levels: asymptomatic, mild, moderate, severe and critical, which can lead to death. One of the most affected Brazilian states was Amazonas, with more than 14 thousand deaths until May 2021, highlighted by the health collapse in health services and the emergence of a new variant called Gama (P.1). Objective: To describe the clinical manifestations, epidemiological profile and vaccination schedule of blood donors from Hemocentro do Amazonas who had Covid-19. Methodology: This is a cross-sectional study, in which blood donors were included, previously confirmed positive for anti-SARS-CoV-2 IgG, from January 2020 to December 2021. Results: Of the 247 blood donors, the main results showed the prevalence of males (77.73%), aged between 31 and 50 years old (58.30%), blood type and Rh O+ factor (54.25%), who lived with two to three people (50.20%); the majority (21,86%) in the north of Manaus, with a monthly income of up to two minimum wages (63.56%). The prevalent clinical manifestations of Covid-19 in blood donors were: loss of taste (52.23%), fever (47.77%) and headache (46.15%). The duration of days of clinical symptoms in blood donors was up to ten days in 116 (46.96%); and only three reported having symptoms for more than 50 days. Only 51 (20.64%) blood donors received vaccines against Covid-19, with a prevalence (86.27%) of the CoronaVac vaccine. Conclusion: It was evident that the clinical symptoms of Covid-19 in blood donors were mild to moderate